Antecedents of Sponsorship-Brand Purchase Intention in Esports Tournaments - Riyadi, Ilham; Kurniawati, Kurniawati; Masnita, Yolanda (Jurnal Economic Resource, 2025)
The esports tournament industry is growing rapidly with an ever-increasing number of spectators and investors. This popularity opens up opportunities for brands to reach consumers through sponsorship. This study aims to identify the factors that affect the purchase intention of esports tournament fans toward sponsorship. This study uses a descriptive method with a quantitative approach. Data was collected through a questionnaire from 270 individuals who participated in or supported esports event tournaments. The results of the study show that esports fan identity, brand fan identity, Community and Sponsorship, satisfaction with the event, esports event attachment, and Attitude towards sponsorship affect Brand Purchase Intention.